Risk of neoplastic change in large gastric hyperplastic polyps and recurrence after endoscopic resection - Forté, Emmanuel; Petit, Bérénice; Walter, Thomas; Lépilliez, Vincent; Vanbiervliet, Geoffroy; Rostain, Florian; Barsic, Neven; Albeniz, Eduardo; Gete, Gonzalo Gonzalez; Gabriel, Jose Carlos Marín; Cuadrado-Tiemblo, Cristina; Ratone, Jean-Philippe; Jacques, Jérémie; Wallenhorst, Timothée; Subtil, Fabien; Albouys, Jérémie; Giovannini, Marc; Chaussade, Stanislas; Landel, Véréna; Ponchon, Thierry; Saurin, Jean-Christophe; Barret, Maximilien; Pioche, Mathieu (Endoscopy, 2020)
Background Gastric hyperplastic polyps (GHPs) have a risk of neoplastic transformation reaching 5 %. Current endoscopic resection techniques appear suboptimal with a high risk of local recurrence. This study assessed the outcomes of endoscopic resection for GHPs and identified risk factors for recurrence and neoplastic transformation.Methods This retrospective, multicenter, European study included adult patients with at least one GHP ≥ 10 mm who underwent endoscopic resection and at least one follow-up endoscopy. Patients with recurrent GHPs or hereditary gastric polyposis were excluded. All data were retrieved from the endoscopy, pathology, and hospitalization reports.Results From June 2007 to August 2018, 145 GHPs in 108 patients were included. Recurrence after endoscopic resection was 51.0 % (74 /145) in 55 patients. R0 resection or en bloc resection did not impact the risk of polyp recurrence. In multivariate analysis, cirrhosis was the only risk factor for recurrence (odds ratio [OR] 4.82, 95 % confidence interval [CI] 1.33 – 17.46; P = 0.02). Overall, 15 GHPs (10.4 %) showed neoplastic transformation, with size > 25 mm (OR 10.24, 95 %CI 2.71 – 38.69; P < 0.001) and presence of intestinal metaplasia (OR 5.93, 95 %CI 1.56 – 22.47; P = 0.01) being associated with an increased risk of neoplastic transformation in multivariate analysis. Conclusions Results confirmed the risk of recurrence and neoplastic transformation of large GHPs. The risk of neoplastic change was significantly increased for lesions > 25 mm, with a risk of high grade dysplasia appearing in polyps ≥ 50 mm. The risk of recurrence was high, particularly in cirrhosis patients, and long-term follow-up is recommended in such patients.